Nilai-Nilai Pendidikan Islam Pada Lempu’ Na Getteng: Upaya Pembentukan dan Implementasi Karakter Jujur Pada Keluarga Masyarakat Bugis di Kelurahan Manding Kecamatan Polewali Kabupaten Polewali Mandar - Muhammad Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the Islamic educational values contained in the Bugis life philosophy known as Lempu’ na Getteng, as well as the efforts to form and implement honest character within Bugis families in Manding Sub-district, Polewali District, Polewali Mandar Regency. This research employs a qualitative methodology with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving traditional leaders, religious figures, community leaders, youth leaders, and Bugis families in the Binangaliu neighborhood. The results indicate that: (1) Lempu’ na Getteng embodies three core Islamic educational values, namely the values of tauhid/akidah (monotheism/faith), akhlak (morality), and kemasyarakatan (social-communal relations); (2) The effort to build honest character is carried out through cultural habituation, family education, and the preservation of Bugis oral literature including pappaseng and warekkada, which encompasses three dimensions of honesty — lempu’ lao ri dewata sewwae (honesty rooted in awareness of Allah’s supervision), lempu’ ri padanna rupa tauwwe (honesty toward fellow human beings), and lempu’ ri aleta (honesty toward oneself); (3) The implementation of Lempu’ na Getteng values in family education is carried out through modeling, habituation, and emotional communication that strengthen spiritual and moral bonds between parents and children. This study concludes that Lempu’ na Getteng is a representation of Islamic educational values within a local wisdom framework that is relevant and contextual in shaping a generation of Bugis with honest, moral, and high-integrity character.